Implementasi Pancasila dalam penegakan hak asasi manusia di Indonesia: Pancasila, Implementasi, Hak asasi manusia , nilai penegakan, indonesia - Ramadhan, A. Maky (Maliki Interdisciplinary Journal, 2025)
In general, Pancasila is the ideological foundation of the Indonesian state, encompassing five principles: Belief in One Almighty God, Just and Civilized Humanity, the Unity of Indonesia, Democracy Guided by the Wisdom of Deliberation/Representation, and Social Justice for All Indonesian People. In the context of human rights, this could highlight how the concept of human rights based on the values ​​and principles of Pancasila is implemented and interpreted. It might also discuss how human rights are guaranteed and protected within the framework of Pancasila in Indonesia, and there might be a discussion about the harmonization between universal human rights values ​​and Pancasila values ​​in practice. However, these are all just general estimates, and it would be better to directly search for related journals or articles for more specific and in-depth information on the topic.